2005
DOI: 10.6090/jarq.39.37
|View full text |Cite
|
Sign up to set email alerts
|

Potential Chemopreventive Properties and Varietal Difference of Dietary Fiber from Sweetpotato (Ipomoea batatas L.) Root

Abstract: The potential chemopreventive properties of the dietary fiber prepared from sweetpotato (Ipomoea batatas L.) roots were examined to promote the demand of this residue from the starch industry. Dietary fiber was prepared by treating starch granules-removed residue with α-amylase. The dietary fibers at 1% concentration enhanced the growth of Bifidobacterium adolescentis and Bifidobacterium breve in vitro among 5 species of Bifidobacterium, which exist in the human intestinal tract. Analysis of the components of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 24 publications
0
19
1
Order By: Relevance
“…The 1 H NMR spectrum showed the anomeric proton as a doublet at 4.74 ppm with coupling constant J 1,2 ϭ 4.8 Hz. Furthermore, the 13 C NMR spectra revealed that the transglycosylation product was found to be consistent with a methyl ␤-L-arabinofuranoside (Ara-Me) (16). These data indicated that HypBA1 is a retaining enzyme.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…The 1 H NMR spectrum showed the anomeric proton as a doublet at 4.74 ppm with coupling constant J 1,2 ϭ 4.8 Hz. Furthermore, the 13 C NMR spectra revealed that the transglycosylation product was found to be consistent with a methyl ␤-L-arabinofuranoside (Ara-Me) (16). These data indicated that HypBA1 is a retaining enzyme.…”
Section: Resultsmentioning
confidence: 65%
“…The elution was monitored by a refractive index (RI) detector (RI-8022, TOSOH), and the fraction that contained the transglycosylation product was collected. 1 H and 13 C NMR spectra were measured with a JMM-ECA600KS spectrometer (JEOL).…”
mentioning
confidence: 99%
“…Oligosccharides and peptides are known to stimulate growth of Bifidobacterium (Kehagias et al, 1977;Cummings et al, 2001). It was reported that dietary fiber from sweet potato effectively stimulates in vitro growth of B. adolescentis and B. breve, which can be found in the human intestinal tract (Yoshimoto et al, 2005). In that report, the growth-stimulating factors in dietary fiber from sweet potato were not determined, although it was suggested that pectin and hemicellulose were involved.…”
mentioning
confidence: 98%
“…PYF medium comprised 10 g Trypticase Peptone, 5 g yeast extract, 0.5 g L-cysteine hydrochloride, 40 mL digested horse blood, and 40 ml salt solution per 1 L. The salt solution contained 0.2 g CaCl 2 , 0.2 g MgSO 4 ·7 H20, 1.0 g KH 2 PO 4 , 1.0 gK 2 HPO 4 , 10 g NaHCO 3 , and 2.0 g NaCl in 1 L deionized water (pH7.6) (Yoshimoto et al 2005).…”
Section: Preparation Of Growth Mediummentioning
confidence: 99%
“…All the bacteria were grown in duplicate fermentations in the appropriate basal medium. Aliquots, (5 ml for fibre analysis and 2 ml for SCFA analysis) were removed for analysis at 0, 6, 24 and 48 h after incubation (Yoshimoto et al 2005;Jaskari et al 1998). …”
Section: In Vitro Fermentationmentioning
confidence: 99%